Development and Validation of a Wave-Propelled Semi-submersible Unmanned Vehicle - Tian Yingyuan; Li Weijia; Wang Zhigang (Polish Maritime Research)
Ocean observation and exploration technologies are crucial for marine environmental protection and resource development, but traditional tools have limitations in terms of operating time, coverage, and cost. Wave gliders, which offer advantages such as long duration, wide range, and low cost, are a promising solution, but their low speed and weak manoeuvrability hinder their application, due to poor collision avoidance and survivability. This study proposes a novel wave-propelled semi-submersible unmanned vehicle (WPSUV) to overcome these disadvantages. The WPSUV features a submerged main structure for navigation and autonomous collision avoidance through rapid buoyancy adjustment. Modelling, computational hydrodynamic and motion simulations, and functional and performance testing at sea demonstrate the feasibility and superior performance of the WPSUV compared to conventional wave gliders. The proposed WPSUV significantly enhances collision avoidance through diving, reduced visual target and wind resistance with minimal structures above the waterline, and improved stability due to its lower centre of gravity. This slightly positively buoyant vehicle with a high lift-to-drag ratio can effectively harness wave kinetic energy and achieve favourable wave-following characteristics. In addition, the submerged main structure provides protection against surface hazards and allows for stealthy operation. This novel wave-propelled and near-surface unmanned underwater vehicle has the potential to revolutionise marine observation and exploration, and to enable safe, reliable, and long-term monitoring of the marine environment.